Guide to American graduate schools - Harold R Doughty (Penguin Books, 1994)
The book provides comprehensive, up-to-date information on every aspect of graduate study, including: *) enrollments, locations, and housing situations for more than 1,200 accredited institutions. *) fields of study offered by each institution. *) admissions and degree requirements. *) opportunities for financial aid and grants; including details on scholarships, fellowships, assisstantships, interships, and traineeships